PEMANFAATAN TEKNIK DELPHI DALAM PENYUSUNAN KOMPETENSI LULUSAN PENDIDIKAN KEJURUAN - Mahfud Effendi, Moh. (Universitas Ahmad Dahlan, 2011)
Competence of graduates of vocational education should meet the needs of the individual students, of society, and of business. Thus, in determining and preparing these competencies should consider the needs of users and the development of graduates, if not then certainly the graduates produced is not absorbed by the business or industry. The number of users of vocational education graduates is problematic in the preparation of competence, hence the Delphi Technique as a needs assessment can be used. Delphi technique is a technique to find solutions through consensus by giving kuisener iteratively to many respondents without a meeting or discussion.